God-optional religion in twentieth-century America: Quakers, Unitarians, reconstructionist Jews, and the crisis over theism - May, Isaac Barnes (Oxford University Press, 2023)
"This book is about the relationship between the American religious left and secularization. It explores how three liberal religions -liberal Quakers, Unitarians, and Reconstructionist Jews- attempted to preserve their traditions in the modern world by redefining what it meant to be religious. Between the 1920s and the 1960s, these groups underwent the most massive theological change imaginable, allowing their members to opt not to believe in a personal God. As the God of traditional theism did not seem to fit into a post-Darwinian framework, these traditions took the dramatic step of redefining that concept to make a "God" that did fit, and eventually they went even further by making belief in God a matter of purely personal preference. This book narrates how, over the course of the twentieth century, believing in God and being religious became increasingly disconnected. It documents the continuance of these religious communities even after the theological rationales that originally brought them together disappeared, their communal identities instead becoming focused on humanitarian service and political commitments, which began to replace a shared adherence to theism. The radical religious views of these small liberal denominations became influential among the wider society, and eventually became accepted in American popular culture and law"--